EVALUATION OF INFRASTRUCTURE READINESS IN SUPPORTING THE IMPLEMENTATION OF E-GOVERNMENT USING THE COBIT 5 FRAMEWORK. CASE STUDY: PADANGSIDIMPUAN CITY GOVERNMENT: English - Alfiansyah Halomoan Siregar; Irman Hermadi; Sri Wahjuni (Faculty of Computer Science Universitas Indonesia, 2019)
The application of information technology (IT) has now become a necessity in all aspects of both individuals, groups or organizations and even government institutions. The implementation of IT in government is a form of execution of the President's instruction No. 3 of 2003 concerning national policies and strategies for the development of e-government. IT infrastructure itself is a foundation and framework that supports a system or organization. Excellent IT infrastructure support will contribute to accelerating the achievement of organizational goals. Evaluation of IT infrastructure readiness in Diskominfo in Padangsidimpuan City is done using the COBIT framework, by measuring the maturity level of IT infrastructure governance that refers to IT management goals number 10 and 11 in COBIT that are mapped on 13 COBIT process domains. The results of the evaluation of the level of achievement in each process there are eight processes at the completion of levels 1 and five are at the achievement of level 0. The level of hope for achieving the whole process is at level 3 and the gap consists of 2 degrees and 3 levels of achievement. The recommendations given in the form of a SWOT in this study aim to increase the level of maturity of IT infrastructure governance to support the implementation of e-government in the city government of Padangsidimpuan.